Comparison of magnetic resonance feature tracking for systolic and diastolic strain and strain rate calculation with spatial modulation of magnetization imaging analysis. Issue 4 (28th March 2014) - Moody, William E.; Taylor, Robin J.; Edwards, Nicola C.; Chue, Colin D.; Umar, Fraz; Taylor, Tiffany J.; Ferro, Charles J.; Young, Alistair A.; Townend, Jonathan N.; Leyva, F.; Steeds, Richard P.
<x xml:space="preserve">Abstract</x> Purpose To compare cardiovascular magnetic resonance‐feature tracking (CMR‐FT) with spatial modulation of magnetization (SPAMM) tagged imaging for the calculation of short and long axis Lagrangian strain measures in systole and diastole. Materials and Methods Healthy controls (n = 35) and patients with dilated cardiomyopathy (n = 10) were identified prospectively and underwent steady‐state free precession (SSFP) cine imaging and SPAMM imaging using a gradient‐echo sequence. A timed offline analysis of images acquired at identical horizontal long and short axis slice positions was performed using CMR‐FT and dynamic tissue‐tagging (CIMTag2D). Agreement between strain and strain rate (SR) values calculated using these two different methods was assessed using the Bland–Altman technique. Results Across all participants, there was good agreement between CMR‐FT and CIMTag for calculation of peak systolic global circumferential strain (−22.7 ± 6.2% vs. −22.5 ± 6.9%, bias 0.2 ± 4.0%) and SR (−1.35 ± 0.42 1/s vs. −1.22 ± 0.42 1/s, bias 0.13 ± 0.33 1/s) and early diastolic global circumferential SR (1.21 ± 0.44 1/s vs. 1.07 ± 0.30 1/s, bias −0.14 ± 0.34 1/s) at the subendocardium. There was satisfactory agreement for derivation of peak systolic global longitudinal strain (−18.1 ± 5.0% vs. −16.7 ± 4.8%, bias 1.3 ± 3.8%) and SR (−1.04 ± 0.29 1/s vs. −0.95 ± 0.32 1/s, bias 0.09 ± 0.26 1/s). The weakest agreement was for early diastolic global longitudinal SR (1.10 ± 0.40 1/s vs. 0.67 ± 0.32 1/s, bias −0.42 ± 0.40 1/s), although the correlation remained significant (r = 0.42, P < 0.01). CMR‐FT generated these data over four times quicker than CIMTag. Conclusion There is sufficient agreement between systolic and diastolic strain measures calculated using CMR‐FT and myocardial tagging for CMR‐FT to be considered as a potentially feasible and rapid alternative. J. Magn. Reson. Imaging 2015;41:1000–1012. © 2014 Wiley Periodicals, Inc.